ANALYSIS OF DISSOLVED PROTEIN CONTENT ON PROTEIN HYDROLYZATES OF CUNANG FISH (Congresox talabon) USING THE BRADFORD METHOD - Anggi Angelita Hermay; Edison Edison; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTCunang fish is one of the sea fish which is rich in protein. The meat found in cunang fish is useful in making fish protein hydrolyzates. This study aims to look at the protein hydrolyzate of cunang fish based on dissolved protein. The research methods used were experimental and non-factorial Completely Randomized Design (CRD). The treatments used were different papain enzymes: 2% (P1), 4% (P2) and 6% (P3). The parameters observed consisted of analysis of dissolved protein by Bradford method on protein hydrolyzate of cunang fish. The results showed that the proximate levels of cunang fish meat was ash 15,15%, water content 73,95%, protein content 73,15% and fat content 1,93%. The concentration of papain enzyme had a significant effect on the dissolved protein content of cunang fish protein hydrolyzate, with the value of dissolved protein content P1 was 7.30%, P2 was 8.77% while P3 was 11.64%.Keyword: fish protein hydrolyzate, papain enzyme, bradforod